Analisis Kritis dan Pengembangan Teknik Modelling Berbasis Islami - Fitria Husna; Nurjannah (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
This paper aims to reconstruct the concept of "modelling" which is part of Albert Bandura's social learning theory by conducting criticism and development based on Islam. The method used in this research is a qualitative method with a type of library research. The results of this study found that there were several deficiencies in the concept of "behavioural" modelling: first, often ignoring one aspect of development and ignoring nature or potential in the heredity of an individual's mental processes. Secondly depending on the pattern formed, success depends on the result. Islamic-based modelling is developed using the mauidzah hasanah approach, which aims to leave an impression on the individual's heart (subliminal massage) and move individuals to do modelling. The various applications in al-uswah, al-qudwah, and al-tadbiq are applied to achieve principles and principles in social learning and to achieve the ultimate goal of self-cleaning, namely takhalli, tahalli, and tajalli.